Assessing the Role of Irrigation as an Adaptive Measure to Climate Change Induced Water Insecurity: Case Study of the Market Gardening Sector in Parts of the Northwest and West Regions of Cameroon - Awazi, Nyong Princely (Frontiers in Water, 2022)
Climate change induced extreme weather events are having major repercussions on availability and accessibility to water and water resources especially for farmers across the globe. This is more so for small-scale farmers in the developing world who largely depend on rain-fed agriculture. The market gardening sector in particular is known for its high dependence on suitable weather conditions for adequate productivity. However, in recent years, market garden crop cultivation has been severely threatened by climate change induced extreme weather events such as prolong dry spells, scanty and erratic rainfall, rising temperatures, extreme sunshine and storms. This study was undertaken to understand the role of irrigation as an adaptive measure to climate change induced water insecurity, with focus on the market gardening sector in parts of the west and northwest regions of Cameroon. Data were collected through a survey of 260 market gardeners involved in different irrigation practices geared toward countering water insecurity problems induced by climate change. Findings indicated that water insecurity is induced by extreme weather events such as prolong dryness, scanty and erratic rainfall, extreme sunshine and rising temperatures. A majority of the market gardeners surveyed reported the existence of water insecurity which has led to crop failure in many instances placing them in financial difficulties and seriously hampering their livelihood. Market gardeners were involved in different types of irrigation practices including sprinkler, drip, furrow, and manual with some taking to no irrigation practice. The main factors influencing market gardeners' practice of irrigation in the face of extreme weather induced water scarcity/insecurity were household income, age of market gardeners, educational level, farm size, number of farm plots, proximity to source of water, gender, water requirement of crop, support from government and NGOs, extension services, access to credit, membership in farming group and membership in common initiative group (CIG). Climate change has therefore induced water insecurity forcing market gardeners to indulge in different irrigation practices all year round in a bid to improve crop productivity and reduce recurrent crop failures. On the basis of these findings, the use of more sustainable irrigation methods in order to conserve water and water resources is recommended as this will go a long way to phase out the problem of water insecurity induced by climate change. Policy makers need to craft and implement favorable policies that encourage more market gardeners to adopt sustainable irrigation practices in the face of climate change induced water scarcity/insecurity.